PENGARUH PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR - Nidaul Hasanah; Nadiah Nadiah (STIT AL-AMIN KREO TANGERANG, 2023)
This research is motivated by one of the factors for the growth of learning motivation that can encourage from outside and from within a person to be able to do a good action, namely less than optimal parental attention. Supervision and direction from parents will affect children in following lessons at school. This research aims: to measure how much influence parental attention has on learning motivation at MI Al-Hidayah UKA. The method used is a type of Quantitative Research with a Descriptive Correlational Analytic method. Sampling technique using Simple random sampling, with a total of 57 students. The results showed that when viewed in terms of coefficient tests Product Moment produce